Functionally active TRPA1 ion channel is downregulated in peptidergic neurons of the Edinger-Westphal nucleus upon acute alcohol exposure - Al-Omari, Ammar; Kecskés, Miklós; Gaszner, Balázs; Biró-Sütő, Tünde; Fazekas, Balázs; Berta, Gergely; Kuzma, Mónika; Pintér, Erika; Kormos, Viktória (Frontiers in Cell and Developmental Biology, 2023)
Introduction: The centrally projecting Edinger-Westphal nucleus (EWcp) contributes to the control of alcohol consumption by its urocortin 1 (UCN1) and cocaine- and amphetamine-regulated transcript (CART) co-expressing peptidergic neurons. Our group recently showed that the urocortinergic EWcp is the primary seat of central nervous system transient receptor potential ankyrin 1 (TRPA1) cation channel mRNA expression. Here, we hypothesized that alcohol and its metabolites, that pass through the blood-brain barrier, may influence the function of urocortinergic cells in EWcp by activating TRPA1 ion channels. We aimed to examine the functional activity of TRPA1 in EWcp and its possible role in a mouse model of acute alcohol exposure. Methods: Electrophysiological measurements were performed on acute brain slices of C57BL/6J male mice containing the EWcp nucleus to prove the functional activity of TRPA1 using a selective, potent, covalent agonist JT010. Male Trpa1 knockout (KO) and wild-type (WT) mice were compared with each other in the morphological studies upon acute alcohol treatment. In both genotypes, half of the animals was treated intraperitoneally with 1g/kg 6% ethanol vs. physiological saline-injected controls. Transcardial perfusion was performed 2 hours after the treatment. In the EWcp area, FOS immunohistochemistry was performed to assess neuronal activation. Trpa1, Cart and Ucn1 mRNA expression as well as UCN1 and CART peptide content was semi-quantified by RNAscope in situ hybridization combined with immunofluorescence. Results: JT010 activated TRPA1 channels of the urocortinergic cells in acute brain slices. Alcohol treatment resulted in a significant FOS activation in both genotypes. Alcohol decreased the Trpa1 mRNA expression in WT mice. The assessment of UCN1 peptide immunoreactivity revealed lower basal UCN1 in KO mice compared to WTs. The UCN1 peptide content was affected genotype-dependently by alcohol: the peptide content decreased in WTs while it increased in KO mice. Alcohol exposure influenced neither Cart and Ucn1 mRNA expression nor the EWcp/CART peptide content. Conclusion: We proved the presence of functional TRPA1 receptors on UCN1 neurons of the EWcp. Decreased Trpa1 mRNA expression upon acute alcohol treatment, associated with reduced neuronal UCN1 peptide content suggesting that this cation channel may contribute to the regulation of the UCN1 release.